OVERVIEW OF RUSSIAN CIVIL JUSTICE - D. Maleshin (BRICS Law Journal, 2017)
Contemporary Russian civil procedure is not a pure Continental model because it also has procedural features of the common law system, as well as some other original and exceptional features. This article examines the main aspects of Russian civil justice: its main principles; judicial organization, including the structure of the courts and the division between courts of general jurisdiction and arbitrazh (commercial) courts, and the Intellectual Property Court; sources of procedural law; bar organization; the jurisdiction of the courts; actions and proceedings; legal costs; evidence; administrative procedure; class actions; enforcement proceedings; and arbitration and mediation.